Dinamika Kebijakan Publik dalam Perlindungan Data Pribadi dan Implikasinya terhadap Hak Sosial Masyarakat Digital - Yoga Saputra Hidayat; Ilham Maulana Firdaus (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
The rapid expansion of digital technology has significantly transformed how data is collected, processed, and utilized, raising critical concerns regarding personal data protection and its implications for social rights in digital societies. In Indonesia, the accelerated growth of digital services has not always been accompanied by adequate data protection mechanisms, leading to increasing risks of privacy violations and data breaches. This study aims to evaluate the quality of public policy on personal data protection and to analyze its implications for the protection of social rights in the digital society. The research employs a mixed-method policy evaluation approach that integrates normative legal analysis with empirical assessment using a multidimensional scoring model. The evaluated dimensions include legal substance, transparency, accountability, implementation, enforcement, supervision, public participation, and social protection. The results show that legal substance achieved the highest score of 80, followed by transparency (72) and accountability (70), while implementation (65), enforcement (60), and supervision (58) indicate weaker performance. Gap analysis reveals significant discrepancies between ideal and actual conditions, particularly in supervision and enforcement. Furthermore, the distribution of social impact shows that vulnerable groups (58), children and adolescents (60), and the elderly (55) receive lower levels of protection compared to general users (72) and business actors (78). These findings indicate that policy effectiveness remains uneven due to limitations in institutional capacity and implementation, highlighting the need for more inclusive and balanced data protection governance.